University Ethics: How Colleges Can Build and Benefit from a Culture of Ethics - Duns, Ryan G (Asian Horizons, 2016)
Keenan, a well-published priest and ethicist, writes University Ethics in the wake of the clergy sexual abuse scandal that has rocked the Catholic Church in America. He detects an analogy in the way Church and University both emphasize vertical accountability over horizontal. Priests and professors are accountable to none but the “man upstairs,” whether that “man” be a bishop or one’s department chair or president. Keenan draws on the model of “fiefdoms” to convey this. Faculty work alone, answer to those above them, and are organized into departments operating independently from one another. The University landscape parodies Tertullian: “What has History to do with Chemistry?” but the effect of this fragmentation is no joke.